PROBLEMS OF PRESERVING NAVOI'S POETICS IN THE PROCESS OF TRANSLATION - Elmuradova Surayyo Abdijalilovna (Sciental Journals Publishing, 2025)
This article analyzes recent achievements and pressing challenges related to the translation of Alisher Navoi’s works into foreign languages. Based on the principles of translation theory, the study explores the ways of accurately conveying Navoi’s literary heritage to an international audience.
Keywords: Alisher Navoi, translation, foreign languages, literary work, problem, innovation, translator.